The Process Of Quality Education - As A Mechanical Combination Of Teaching And Learning Processes - Rustam Abdullayev (Procedia of Social Sciences and Humanities, 2022)
Quality education depends on the fact that students are well educated. Therefore, the educational process is a combination of educational and pedagogical tasks. One of the factors confirming the integrity of the educational and pedagogical tasks of education is the fact that teaching methods are expressed as an integral part of teaching methods, and secondly, educational methods themselves are manifested as methods of motivating learning.